2019
DOI: 10.1039/c8fo01123k
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A inhibits the action of LPS on the intestinal epithelial barrier function and tight junction proteins

Abstract: Inflammation caused by either intrinsic or extrinsic toxins results in intestinal barrier dysfunction, contributing to inflammatory bowel disease (IBD) and other diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
96
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(108 citation statements)
references
References 28 publications
8
96
0
4
Order By: Relevance
“…Studies have confirmed that LPS, one commonly and important inflammation activator, produces damages on tight junctions in vitro (Chen et al, ; Main, Weber, Baumgard, & Gabler, ). Previously, we have shown that VA protected against LPS‐induced damage on tight junctions in vitro (He et al, ). However, whether or how effect of VA on tight junction of intestine in vivo remains elusive.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Studies have confirmed that LPS, one commonly and important inflammation activator, produces damages on tight junctions in vitro (Chen et al, ; Main, Weber, Baumgard, & Gabler, ). Previously, we have shown that VA protected against LPS‐induced damage on tight junctions in vitro (He et al, ). However, whether or how effect of VA on tight junction of intestine in vivo remains elusive.…”
Section: Introductionmentioning
confidence: 81%
“…Recently, it has been reported that the development of inflammation ‐caused diseases is associated with alteration of intestinal tissue proteins, particularly tight junction proteins (Yang et al, ). Our previous study has shown that VA inhibits the action of LPS on the intestinal epithelial barrier function and tight junction proteins at cellular level (He et al, ). However, it is unknown whether this protective effect of VA could be seen in vivo or not.…”
Section: Discussionmentioning
confidence: 99%
“…TJs can be compromised by luminal noxious antigens, one of which is lipopolysaccharides (LPS), the main component of the outer membrane of Gram-negative bacteria. Growing investigations indicate that LPS triggers an inflammatory signaling cascade to reduce tight junction protein expression, leading to increased intestinal permeability and disrupting intestinal epithelial barrier function (He et al, 2019;Tunisi et al, 2019). Clinical study also demonstrated that circulating blood LPS levels are elevated in Crohn's disease and sepsis patients, and contribute to the pathogenesis of intestinal and systemic inflammatory response (Guo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that β-carotene can promote gap junctional intercellular communication [15]. Another study also demonstrated that Vitamin A recovered LPS-induced in ammation-mediated intestinal barrier dysfunction and re-boosted LPS-induced decreases of ZO-1, Occludin and Claudin-1 at the tight junctions in IPEC-J2 cells [36]. Therefore, these data suggest that β-carotene increases TJ protein expression and improves epithelial barrier function in the intestine.…”
Section: Discussionmentioning
confidence: 63%